2008
DOI: 10.1007/s11707-009-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental geochemistry of high arsenic groundwater at western Hetao plain, Inner Mongolia

Abstract: Environmental geochemistry of high arsenic groundwater at Hetao plain was studied on the basis of geochemical survey of the groundwater and a core sediment. Arsenic concentration in groundwater samples varies from 76 to 1093 μg/L. The high arsenic groundwater mostly appears to be weakly alkaline. The concentrations of NO -3 and SO 2 -4 are relatively low, while the concentrations of DOC, NH þ 4 , dissolved Fe and sulfide are relatively great. Analysis of arsenic speciation in 21 samples shows that arsenic is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…This was consistent with the results by He (2010) that As in soils or sediments could be leached into groundwater with the irrigation return flow. The 17 groundwater samples were divided into two groups with the distinctive geochemical characteristics according to the PCA ( Figure 2A ) and Hierarchical clustering results ( Figure 2B ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This was consistent with the results by He (2010) that As in soils or sediments could be leached into groundwater with the irrigation return flow. The 17 groundwater samples were divided into two groups with the distinctive geochemical characteristics according to the PCA ( Figure 2A ) and Hierarchical clustering results ( Figure 2B ).…”
Section: Resultssupporting
confidence: 93%
“…Agricultural activities such as N-fertilizer application and irrigation might also play important roles in As release and mobilization (Busbee et al, 2009; Mayorga et al, 2013). The reasonable explanation might be that the irrigation and drainage processes could leach As and dissolved organic matter from surficial sediments to the underlying aquifer, which caused the biogeochemical changes (He, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, high arsenic-bearing groundwater mainly exists in Inner Mongolia, Shanxi, Xinjiang, etc., including 40 counties of eight provinces. For example, arsenic concentration in groundwater samples collected from the Hetao Plain in the Inner Mongolia Autonomous Region, Datong in Shanxi province, and Dzungaria district in Xinjiang province can be up to 1.09 mg/L [7], 1.82 mg/L [8], and 0.85 mg/L [9], respectively. It is obvious that the highest concentration of arsenic in arsenic-bearing groundwater in different regions in China can reach, or exceed, 1 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…However, high concentrations of arsenic (As > 10 µg/L) in groundwater are frequently found in China, India, Nepal, Bangladesh, and other countries [3,[7][8][9]. Chakraborti et al [10] investigated the arsenic contamination of groundwater in Patna district (Bihar, India); the study detected a maximum arsenic concentration of 1466 µg/L and found that 61% and 44% of tube-wells contained arsenic at concentrations that exceeded 10 µg/L and 50 µg/L, respectively.…”
mentioning
confidence: 99%